2017
DOI: 10.4085/1062-6050-52.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sport-Related Concussions in High School Athletes: National Athletic Treatment, Injury and Outcomes Network (NATION), 2011–2012 Through 2013–2014

Abstract: academic years.Main Outcome Measure(s): Sport-related concussion counts, percentages, rates per 10 000 athlete-exposures (AEs), rate ratios (RRs), and injury proportion ratios (IPRs) were reported with 95% confidence intervals (CIs). Rate ratios and IPRs with 95% CIs not containing 1.0 were considered significant.Results: Overall, 2004 SRCs were reported among 27 high school sports, for a rate of 3.89 per 10 000 AEs. Football had the highest SRC rate (9.21/10 000 AEs), followed by boys' lacrosse (6.65/10 000 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(185 citation statements)
references
References 49 publications
9
167
4
Order By: Relevance
“…Sports‐injury literature has also focused on head injuries and the range of clinical symptoms they can provoke. Recent studies in college athletes following concussion have shown an occurrence of dizziness and hyperacusis in up to 75% and 40% of individuals, respectively . Interestingly, these symptoms were also associated with duration of concussion symptoms and prolonged return to competition .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sports‐injury literature has also focused on head injuries and the range of clinical symptoms they can provoke. Recent studies in college athletes following concussion have shown an occurrence of dizziness and hyperacusis in up to 75% and 40% of individuals, respectively . Interestingly, these symptoms were also associated with duration of concussion symptoms and prolonged return to competition .…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies in college athletes following concussion have shown an occurrence of dizziness and hyperacusis in up to 75% and 40% of individuals, respectively. 50,51 Interestingly, these symptoms were also associated with duration of concussion symptoms and prolonged return to competition. 15 Further characterization of hyperacusis in sports-related mTBI patients using hearing threshold and loudness discomfort level testing has also been studied.…”
Section: Fig 4 (A) Percentage Of Mtbi Versus Controls Patients Withmentioning
confidence: 99%
“…Current research suggest that concussion rates are higher for female athletes compared to male athletes when examined on the basis of sports with comparable exposure types [77][78][79][80][81]. The relative risk of concussion in collegiate female athletes compared to male athletes has been reported to range from 53% higher in basketball and 83% higher in soccer to 265% higher in baseball/softball [81].…”
Section: Epidemiologymentioning
confidence: 99%
“…Higher incidence in females [77][78][79][80][81][82][83][84][85][86][87][88][89] Female risk factors include reduced neck girth and strength relative to head size compared to males [88][89][90][91][92][93][94] Females report more symptoms postinjury and have higher rates of postconcussive syndrome [110,111] RED-S ¼ relative energy deficiency in sport; BMI ¼ body mass index; BMD ¼ bone mineral density; BSI ¼ bone stress injury; ACL ¼ anterior cruciate ligament.…”
Section: Concussionmentioning
confidence: 99%
See 1 more Smart Citation